(untitled) (Physical Culture and Sport: Scientific Perspective, 2022)
The article examines the problem of formation and development of pedagogical culture of specialists in various areas of training. General pedagogical approaches to the problem of formation of pedagogical culture are described in detail. The material is presented in a historical perspective. Modern culturology distinguishes approaches to this phenomenon, which consider the dynamics of development and understanding of culture from the perspective of creative self-realization of a specialist, their special way of human activity. In the literature there is a description of three types of cultures: the first group is a system of knowledge and abilities; the second group - values and the relationship of the concept of culture to values and relations; the third group - behavior and lifestyle. This distribution allows the teacher to correctly distribute the functions of each group, to fully realize the educational possibilities of learning. Modern representatives of the humanitarian direction consider different types of culture: "political-legal, artistic-aesthetic, physical, culture of work and everyday life, scientific, moral-normative, communicative, social and pedagogical." A selection of approaches that influence the development of pedagogical culture has been made. Several components of pedagogical culture are highlighted: intellectuality, intelligence, erudition, interest in education, pedagogical experience, critical approach to pedagogical activity, perseverance, collectivism, prudence, purposefulness, optimism. It is shown that the components of pedagogical culture should be inherent to specialists of various fields of training, but especially to teachers. The formation of pedagogical culture is based on general pedagogical approaches, among which are selected: systemic, activity, personal, personal-activity, integration, praxeological, axeological. These approaches are considered in the relationship between the classical presentation of approaches and the peculiarities of pedagogical culture. At the same time, the didactic principles that serve as a basis for pedagogical approaches are considered: scientificity, accessibility, continuity, connection of theory with practice, consistency, professional orientation. Each of the listed principles forms a pedagogical culture, as it is the basis for general pedagogical approaches. In this way, the methodological foundations of the formation of the pedagogical culture of a specialist are presented.